2020
DOI: 10.1186/s42269-020-00447-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonadaceae: Protective against breast cancer?

Abstract: Background Breast cancer is the most common malignancy and one of the leading causes of cancer-linked deaths in women. The development of the mammary gland is regulated by oestrogen whose activities have also been linked with various diseases including breast cancer. Research has shown that host–microbiota relationship plays a role in human health and disease, so we investigated the association between breast microbiota and breast cancer. A search of the literature was conducted using search tools such as Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Of the top 30 genera, Sphingobium was almost only exclusively discovered in healthy individuals. Recent studies have suggested its potential protective role in breast cancer, because of its ability to metabolize oestrogen [53, 54]. Aggregatibacter was more abundant in tumorous patients in our study.…”
Section: Discussionsupporting
confidence: 54%
“…Of the top 30 genera, Sphingobium was almost only exclusively discovered in healthy individuals. Recent studies have suggested its potential protective role in breast cancer, because of its ability to metabolize oestrogen [53, 54]. Aggregatibacter was more abundant in tumorous patients in our study.…”
Section: Discussionsupporting
confidence: 54%
“…2B, C ). The family Sphingomonadaceae , which includes Sphigomonas , was previously suggested to be protective against breast cancer [ 45 ]. The highlighted bacterium in that study was a member of the genus Sphingobium , which we find in 18.3% of healthy esophagi but only a single ESCA sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Sphingobium may play a protective role. Due to its extra ability to metabolize estrogen, it may have favorable influence on outcomes in breast cancer, especially estrogen-positive breast cancer [78,79]. However, the exact roles the pathogens may play in bladder cancer pathology remain to be seen.…”
Section: Discussionmentioning
confidence: 99%